What are the Major Barriers and Challenges Faced by Independent Oil Palm Smallholder Farmers in RSPO Certification? - Citra Irawan, Norbertus; Mahananto; Supriyadi, Teguh; Haryuni (Agribusiness Department, Agriculture Faculty, Tunas Pembangunan University, Surakarta, Indonesia, 2024)
The Roundtable on Sustainable Palm Oil (RSPO) certification is essential for promoting sustainable palm oil production; however, smallholder farmers face significant obstacles in meeting its standards, hindering their growth. This study aims to identify the main barriers and challenges for independent oil palm smallholders in the RSPO certification process and to propose strategies for overcoming these issues. Using a mixed-methods approach, researchers collected data from 60 smallholders through a snowball sampling method and analyzed it using descriptive statistical techniques such as frequency counts and cross-tabulations. Critical barriers identified include high certification costs, lack of knowledge, limited resources, difficulties tracking production yields, and challenges meeting social requirements. Furthermore, smallholders struggle with adapting cultivation practices, accessing markets, maintaining commitment, building capacity, and navigating bureaucratic hurdles. Organizations are urged to adopt market development strategies, enhance their Corporate Social Responsibility (CSR) initiatives, and facilitate better access to sustainable technologies to tackle these challenges. Additionally, enhancing green skills, simplifying record-keeping, reinforcing farmer groups, and offering financial incentives, including soft loans and tailored training, are critical. Streamlining certification procedures will also alleviate administrative burdens, enabling smallholders to adopt sustainable practices more effectively.